Studi Analisis Hadis tentang Niat Menurut Teori Hermeneutika Schleiermacher - Al-Maududi, Abdi; Ismail, Padli; Ridlo, Muhammad Abdurrasyid (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The hadith of the prophet Muhammad SAW has a fundamental role in shaping the framework of values ​​and norms of Muslims. As the second source of Islamic law after the Qur'an, the Hadith is not only a reference in the theological realm, but also has relevance in various aspects of life. One of the most popular Hadith is